The Influence of the Disadvantaged Mindset on System-Justifying Beliefs - Yang, Lihua; Tang, Shujun; Li, Kai (Frontiers in Psychology, 2022)
System justification theory holds that disadvantaged groups rationalize the current social system, although it is unfavorable to them. Epistemic, relational, and existential needs are factors that explain this phenomenon. However, the literature has not yet examined and explained when disadvantaged groups no longer rationalize current social systems. This study uses a questionnaire survey method (N = 745) to study the moderating effect of collectivism on disadvantaged mindset and system-justifying beliefs. It found that collectivism can influence the predictive effect of disadvantaged mindset on system-justifying beliefs. For people who scored low in collectivism, a disadvantaged mindset can significantly negatively predict system-justifying beliefs; for those who scored high in collectivism, a disadvantaged mindset no longer predicts system-justifying beliefs. Therefore, these results show that collectivist values are important for explaining system justification in disadvantaged groups. When collectivist values decline, the level of rationalization of the social system by disadvantaged groups also decreases.